Knowledge of patients of Endoscopy Department on prophylaxis and treatment of large intestine neoplasm - Sapiełkin, Beata; Gotlib, Joanna (Nursing in the 21st Century, 2013)
KNOWLEDGE OF PATIENTS OF ENDOSCOPY DEPARTMENT ON PROPHYLAXIS AND TREATMENT OF LARGE INTESTINE NEOPLASMIntroduction. According to the WHO, 7.5 million people (12.5% of the world population) die from a tumour every year. Large intestine carcinoma is the most frequent malignant neoplasm.Aim. The study aimed to analyse the level of knowledge of patients on the prophylaxis and treatment of neoplastic diseases of the large intestine.Materials and Methods. The study involved 114 patients participating in screening for large intestine neoplasm who were presenting themselves for colonoscopy to Endoscopy Department at One-Day Surgery Hospital due to medical indications. Voluntary and anonymous questionnaire studies, 35 questions, statistical analysis: Statsoft STATISTICA 10.0, Mann-Whitney U test, p